COACHING IN SPORTS GAMES - Florin-Valentin Leuciuc (Editura Univeristatii "Stefan cel Mare" din Suceava, 2018)
The role of sports training is to ensure an optimal development level of motor abilities for athletes, in physiological, physical, technical, tactical, psychological, theoretical terms contributing to good behavior in competitions and the achievement of performance targets. The coaching process is a systemic one that takes into account the entire life of the athletes and the entire context in which they are located and act. This is also why the changes resulting from a coaching process reverberate in all areas of their life. The essence of coaching is to facilitate change, evolution, development of athletes to a higher level so that they reach the performance they wish to get. Coaching method has important meanings in shaping the motivational profile of athletes with a key role in obtaining a high quality of training and achieving performance in competitions.